Esforços de inovação face aos obstáculos institucionais na américa latina: identificando os efeitos da internacionalização acelerada e dos gatilhos relacionais - Bittencourt, Vitor da Silva (2020)
Innovation has become a priority among scholars, politicians and practitioners, but there is still a lack of consensus and convergence in the literature about the factors that determine innovation efforts at the firm level of developing countries. Therefore, the general objective was to verify the extent to which accelerated internationalization and relational triggers enhance the innovation efforts of companies in Latin American countries, in view of the perception of the severity of institutional obstacles. Related to the method, a database from the World Bank (Environment Surveys) which had 14,064 companies from 20 countries in Latin America answering questions related to their innovation efforts. Regarding the results, there was a direct and positive effect of the perception of gravity approaching institutional obstacles, accelerated internationalization and relational triggers in innovation efforts. In addition, the moderating effect of accelerated internationalization was detected in the relationship between institutional obstacles and innovation efforts. That said, it was possible to infer that, by considering the severity of institutional obstacles and then driving their innovation efforts, Latin American companies may be able to move more quickly towards commercial and technological transformations, making use of relational triggers and, consequently, offering more assertive products, processes and investments in R&D, connecting better to specific niches that lack disruptive innovation. This effect can be explained once such companies can use a sharper perception of the severity of institutional obstacles, thus developing innovation efforts based on adaptive or disruptional strategies, also benefiting from the potentializing effect of accelerated internationalization. It is worth mentioning the unpublished contributions, as this is the first time that the perception of seriousness about institutional obstacles is assessed jointly and empirically, as well as the evidence of accelerated internationalization and the use of relational triggers, to explain innovation efforts, considering a large number of firms from Latin American countries. This research is also valuable for demonstrating the potentializing effect of accelerated internationalization in the relationship between institutional obstacles and innovation efforts. The research also contributes to inter- and intra-group analyzes, showing which groups of Latin American companies innovation efforts are most significant and distinctive, and which therefore demand pro-market and pro-international public policies. Finally, the research shows patterns of correlation between age, size, perception of seriousness about institutional obstacles and innovation efforts, highlighting the importance of professionalization, expansion and business maturation programs in Latin America.